Column Flange Strength at Moment End-Plate Connections - Curtis, Larry E.; Murray, Thomas M. (Engineering Journal, 1989)
Current American Institute of Steel Construction (AISC) design recommendations for moment end plate connections are basically limited to the end-plate, bolts, and the compression region of the column side of the connection (AISC). Although specific design procedures for column flange strength at the tension regions of the connection have not been included in AISC design manuals, much research on this topic has been conducted in Europe and the United States. The purpose of this paper is to present design recommendations for required column flange strength at the tension region of the moment end-plate connection configurations. The configuration will be referred to as the 4 bolt stiffened end-plate and as the 8-bolt stiffened end-plate. A design procedure for the latter configuration has recently been published.